Environmental Regulation and the COVID-19 Pandemic: A Review of Regulator Response in Canada - Victoria Goodday (The School of Public Policy Publications, 2021)
Governments worldwide weakened environmental protection in response to the COVID-19 pandemic, including federal and provincial government agencies across Canada. In this briefing paper, I review and analyze these actions, comparing the types of rules changed, types of changes, rationale and sectors impacted. Results show that Canadian regulators took one of two approaches: enforcement discretion or pre-emptive rule adjustment. Industry, government and public stakeholders all benefited from relaxed rules. Most of the rules relaxed, however, were specific to certain industrial sectors: the oil, gas and coal; mining; fisheries and water sectors. Regulators’ main reason for adjusting environmental rules was to address capacity constraints faced by regulated entities, with limited detail provided to justify the changes in most cases. Over a third of the changes were indefinite with no set end date. I discuss implications of these actions, including increased risk of harm to the environment and human health, budgetary impacts, noncompliance enforcement and considerations for regulatory design moving forward.